Influenza and Antibody-Dependent Cellular Cytotoxicity - Von Holle, Tarra A.; Moody, M. Anthony (Frontiers in Immunology, 2019)
Despite the availability of yearly vaccinations, influenza continues to cause seasonal and pandemic rises in illness and death. An error prone replication mechanism results in antigenic drift and viral escape from immune pressure, and recombination results in antigenic shift that can rapidly move through populations that lack immunity to newly emergent strains. The development of a “universal” vaccine is a high priority and many strategies have been proposed, but our current understanding of influenza immunity is incomplete making the development of better influenza vaccines challenging. Influenza immunity has traditionally been measured by neutralization of virions and hemagglutination inhibition, but in recent years there has been a growing appreciation of other responses that can contribute to protection such as antibody-dependent cellular cytotoxicity (ADCC) that can kill influenza-infected cells. ADCC has been shown to provide cross-strain protection and to assist in viral clearance, making it an attractive target for “universal” vaccine designs. Here we provide a brief overview of the current state of influenza research that leverages “the other end of the antibody”.